Combatting Othering and Inspiring Hope: A Unique Approach to Teaching About Juvenile Justice. Issue 3 (3rd July 2018) - VanderPyl, Taryn
Abstract : This case study was conducted to evaluate the experience of students in one university course about juvenile justice and one community partnership working together to create a unique learning experience for two very distinct groups of young adults. One of the groups involved justice-involved young men and their parole officers; the other group involved college students enrolled in the course. University students learned civic engagement is not charity, but rather it is working alongside a community partner toward a joint goal. All participants disrupted the "othering" that commonly exists between two such disparate groups. Finally, the community participants gained hope through experiencing a college course firsthand and being able to see themselves as college students. The success of this collaboration was demonstrated thoroughly through informal feedback, formal reflections, course evaluations, and participant observation.